Implementation of Hidden Curriculum in Modern Islamic Institution: A phenomenology Studies at Pondok Modern Darussalam Gontor Ponorogo Indonesia - Fahrudin, Adi; Alamin, Nurul Salis; Suradika, Agus; Bahri, Saiful (Technium Social Sciences Journal, 2022)
Moral problems of Indonesian youth who are still in the productive age of education on the verge of degradation. The Indonesian Child Protection Commission (KPAI) released data showing that in the time period between 2011 to 2019, there were 37,381 complaints of violence committed by teenagers. This means that, annually, 4153 cases occur in that time interval, and it is a concern that 11% of the total number occurs in the world of education. The formal curriculum in the Indonesian education system does not accommodate the importance of students' moral education. The tendency to increase intellectual intelligence is far more dominant than moral and spiritual intelligence. Theoretically, moral education with the internalization of values is in the hidden curriculum, such as the views of Philip W. Jackson, Elizabeth Vallance, and Henry Giroux. This study aims to find the following: 1. Dimensions of the hidden curriculum in education at Darussalam Gontor Modern Islamic Boarding School, 2 aspects that affect the hidden curriculum in Darussalam Gontor Modern Islamic Boarding School's education, 3. Functions of the hidden curriculum in Darussalam Gontor Modern Islamic Boarding School's education, 4 Implementation of the hidden curriculum in the education of Pondok Modern Darussalam Gontor. This research method is qualitative with a phenomenological approach. Data collection techniques were carried out by interview, observation, and documentation study. Data analysis used an interactive model from Milles & Huberman, namely data reduction, data display, and verification. The wetness of the data was measured using a triangulation of sources and techniques and extended the researcher's participation. The results of this study indicate that: 1. Hidden Curriculum in Pondok Modern Darussalam education is in 5 dimensions; a. Activities, b. Social Structure, c. Discipline, d. Policy, e. Education Milliu. The activity dimension containing elements of a hidden curriculum is more strategic because activities with their diversity have succeeded in creating high dynamics, and high dynamics are able to form militancy, and militancy forms patterns of thought, attitudes, and life skills, especially in terms of leadership. 2. Aspects that affect the hidden curriculum in education Pondok Modern Darussalam Gontor consists of the vision, mission, and goals of education, an Islamic boarding school values, both of which affect the direction and purpose of the hidden curriculum in this cottage, as well as discipline and example, both of which affect the effectiveness of the hidden curriculum in its implementation. Aspects of Islamic boarding school values have a stronger influence on the direction and purpose of the hidden curriculum than any other factor because values are the basis of all movements in this Pondok, as well as discipline and exemplary behavior, both of which are the most dominant aspects affecting the effectiveness of the hidden curriculum at Pondok Modern Darussalam Gontor. 3. The hidden curriculum function in Pondok Modern Darussalam Gontor education is not only to produce graduates who are moral but also very strong in forming a leadership mindset, leadership behavior, and leadership skills. 4 . The implementation of the hidden curriculum in Pondok Modern Darussalam Gontor education uses six approaches, namely: a. Assignment, b. Briefing, c. Supervision, d. Habituation, e. Exemplary, f. Milliu creation. The assignment is the most strategic approach to implementing the hidden curriculum because it has succeeded in exploring all the talents and interests of students and then developing them according to their respective tendencies.